Psychotherapy and religion: The influence of Paul Tillich on Rollo May’s existential psychotherapy - Fernández Jiménez, Lucía Carolina (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
Since psychology obtained its recognition as an autonomous science in the 19th century, it has progressively gained independence from religion, to the extent of adopting a reductionist perspective that denies the spiritual dimension of the human being. Nevertheless, Rollo May´s existential psychotherapy, deeply influenced by the existentialist theologian Paul Tillich, is an example of how the therapeutic practice not only is not opposed to religion, but also can take profit of some of its orientations, that are of vital importance to its task.
Keywords: Paul Tillich; Rollo May; existential psychotherapy; religion; meaning of life; anguish